The Effect Of Leadership On Employee Performance With Work Motivation And Organizational Culture As Intervening Variables (Case Study At PT Agung Solusi Trans) - Edison Sihotang Matanari; Francis Hutabarat (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
This study aims to analyze the influence of leadership on employee performance with work motivation and organizational culture as intervening variables. Data collection uses a quantitative method by distributing questionnaires to employees within PT Agung Solusi Trans. Data collection was obtained by incidental sampling through questionnaires directly to 220 employees, namely the study population and found a sample of 111 respondents. The results of the study show that: leadership has no significant effect on employee performance, work motivation has no significant effect on employee performance, organizational culture has a positive and significant effect on employee performance, leadership has a positive and significant effect on employee motivation, Leadership has a positive and significant effect on organizational culture.